Facilitating Independent Student Learning through a Computer Simulated Animal Dissection : Final Report for a 1996 National Teaching Development Grant. - Bencini, Roberta (Committee for University Teaching and Staff Development (CUTSD), 1998)
This is a final report for a 1996 National Teaching Development Grant funded by the Committee for University Teaching and Staff Development. The project involved the facilitation of independent learning for university agriculture students through a computer simulated animal dissection. The report details the project and provides justification and educational rationale for its development.